Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T17:55:16+01:00
A) (x+√7)(x-√7)= x² - 7
b)(xy²+z)(z-xy²)= (z+xy²)(z-xy²) = z² x²y⁴
c)(x-2√2)(2√2+x)=(x-2√2)(x+2√2) = x² - 8
d)(√5x-y)(y+√5x)= (√5x-y)(√5x+y) = 5 - y²
e)(3√3+x⁴)(x⁴-3√3)= (x⁴+3√3)(x⁴-3√3) = x⁸ - 27
2009-12-07T17:59:48+01:00
A)x2-√49=x2-7
b)z2-x2y4
c)x2-4√4=x2-4*2=x2-8
d)√25x2-y2=5x2-y2
e)x8-9√9=x8-9*3=x2-27

Proszę:)
2009-12-07T18:04:57+01:00
A) (x+√7)(x-√7)=x²
b)(xy²+z)(z-xy²)=xy²z-z²y⁴+z²-xy²z=z²-z²y⁴
c)(x-2√2)(2√2+x)=2√2x+x²-8-2√2x=x²-8
d)(√5x-y)(y+√5x)=√5xy+5x²-y²-√5xy=5x²-y²
e)(3√3+x⁴)(x⁴-3√3)=3√3x⁴-27+x⁸-3√3x⁴=x⁸-27